Drug Safety: Challenges and Solutions - Papoyan, Tatshat («Տնտեսագետ» հրատ․)
Drug safety is a significant healthcare problem with consequences for patient outcomes and quality of care (WHO, 2017). This particular report reviews the different facets of drug safety, in terms of the issues related to the production and distribution, the regulatory authority responsible for drug safety, ADR monitoring and security complaints. A literature review was performed to evaluate the present state of drug safety and to identify challenges and trends. The study also describes research activities. methodology, sources of data and analysis techniques. It is concluded that there are several challenges in drug safety assurance including an increase in counterfeit medicines, lack of regulatory oversight, lack of surveillance of negative effects of drugs on people. The article examines these solutions and challenges, like blockchain, improved accountability and transparency, and better reporting and monitoring of ADRs. The paper also discusses how the findings can contribute to the activities of providers, regulators, and policy makers, and calls for a concerted approach to drug safety problems from policymakers.
Keywords: Management